2019
DOI: 10.1136/bmjopen-2019-029936
|View full text |Cite
|
Sign up to set email alerts
|

Recent adverse mortality trends in Scotland: comparison with other high-income countries

Abstract: ObjectiveGains in life expectancy have faltered in several high-income countries in recent years. Scotland has consistently had a lower life expectancy than many other high-income countries over the past 70 years. We aim to compare life expectancy trends in Scotland to those seen internationally and to assess the timing and importance of any recent changes in mortality trends for Scotland.SettingAustria, Croatia, Czech Republic, Denmark, England and Wales, Estonia, France, Germany, Hungary, Iceland, Israel, Ja… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Drivers for this are complex and multifactorial (with government austerity measures and rising inequality described cited as possible factors). [16][17][18][19] Our results highlight that younger adults with multimorbidity represent an important group at risk of premature mortality. It has been highlighted that reductions in life expectancy are more marked among poorer socioeconomic groups.…”
Section: Open Accessmentioning
confidence: 61%
See 1 more Smart Citation
“…Drivers for this are complex and multifactorial (with government austerity measures and rising inequality described cited as possible factors). [16][17][18][19] Our results highlight that younger adults with multimorbidity represent an important group at risk of premature mortality. It has been highlighted that reductions in life expectancy are more marked among poorer socioeconomic groups.…”
Section: Open Accessmentioning
confidence: 61%
“…Open access countries has stalled and in some cases reversed. [16][17][18][19] Further to this, non-communicable diseases are a significant source of premature mortality, 15 17 indicating that exploration of this for multimorbidity is important.…”
Section: Introductionmentioning
confidence: 99%
“…Life expectancy growth between 2000-2002 and 2012-2014 and between 2012-2014 and 2015-2017 was decomposed into age and cause components using Arriaga's method with the aid of syntax developed by Auger et al 18 19 The break between the two periods was selected on the basis of the previously identified change in mortality trend which showed that the best estimate of when mortality rates changed to a slower rate of improvement was the year to 2012 quarter 4 for men and the year to 2014 quarter 2 for women. 2 As life expectancy data is based on 3-year rolling periods, 2012-2014 was chosen to most accurately reflect this breakpoint. Life expectancy change and decomposition results are presented as annualised change in life expectancy (in weeks) to account for the different length of the two time periods.…”
Section: Methodsmentioning
confidence: 99%
“…The upward trend in life expectancy (LE) across the UK nations stalled around 2012–2014. 1 This stalling presents one the greatest challenges to population health since the 1940s, 2 with the lost gains in LE being similar to the worst case scenario of pandemic COVID-19. 3 4 While a slowdown in improving LE was observed across many high-income countries, it was not seen everywhere, with the UK nations and USA among the worst affected.…”
Section: Introductionmentioning
confidence: 99%